Merger Control as Barrier to EU Banking Market Integration - Matthias Koehler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
In 2005, the President of the Bank of Italy blocked the cross-border acquisition of two Italian banks for ?prudential reasons and formal errors?. Following these events, the EU Commission brought actions against Italy for infringement of the principle of the free movement of capital. Although there is anecdotal evidence that prudential control may constitute a barrier to cross-border M&A in the banking sector, empirical evidence is missing until now. The main problem is the lack of data on the scope for politicians and supervisors to block M&A in the banking sector. The main contribution of this paper is to measure this scope for interference by constructing indices on the political independence and the transparency and strength of the supervisory review process of bank M&A. The main source of information to construct these indices is a questionnaire on banking regulation that was sent to the supervisory authorities in the 25 EU member countries between October 2006 and March 2007.
More recent version: http://hdl.handle.net/10419/29640
Keywords: 330; Fusionskontrolle; Bank; Übernahme; Markteintritt; EU-Binnenmarkt; EU-Staaten; Italien